2020
DOI: 10.1021/acs.biochem.9b01123
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution In Situ NMR Spectroscopy of Bacterial Envelope Proteins in Outer Membrane Vesicles

Abstract: The cell envelope of Gram-negative bacteria is an elaborate cellular environment, consisting of two lipid membranes separated by the aqueous periplasm. So far, efforts to mimic this environment under laboratory conditions have been limited by the complexity of the asymmetric bacterial outer membrane. To evade this impasse, we recently established a method to modify the protein composition of bacterial outer membrane vesicles (OMVs) released from Escherichia coli as a platform for biophysical studies of outer m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 38 publications
2
13
0
Order By: Relevance
“…Chemie states.I ti sr eassuring to confirm the lateral gate,L 3-L8, T1-T6, and the T7-POTRA5d istances corresponding to the different conformations of BamA (which were solved in different detergent micelles) in the native membrane.Atthe same time,i ti sa lso shown that the native environment can populate an equilibrium between those states and may further modulate the structure.Complementary to the developments in the in situ solid-state NMR spectroscopy, [57,58] our approach offers agreat opportunity for further investigations of BamA and the BAMc omplex in the native outer membrane environment.…”
Section: Methodsmentioning
confidence: 98%
“…Chemie states.I ti sr eassuring to confirm the lateral gate,L 3-L8, T1-T6, and the T7-POTRA5d istances corresponding to the different conformations of BamA (which were solved in different detergent micelles) in the native membrane.Atthe same time,i ti sa lso shown that the native environment can populate an equilibrium between those states and may further modulate the structure.Complementary to the developments in the in situ solid-state NMR spectroscopy, [57,58] our approach offers agreat opportunity for further investigations of BamA and the BAMc omplex in the native outer membrane environment.…”
Section: Methodsmentioning
confidence: 98%
“…states.I ti sr eassuring to confirm the lateral gate,L 3-L8, T1-T6, and the T7-POTRA5d istances corresponding to the different conformations of BamA (which were solved in different detergent micelles) in the native membrane.Atthe same time,i ti sa lso shown that the native environment can populate an equilibrium between those states and may further modulate the structure.Complementary to the developments in the in situ solid-state NMR spectroscopy, [57,58] our approach offers agreat opportunity for further investigations of BamA and the BAMc omplex in the native outer membrane environment.…”
Section: Methodsmentioning
confidence: 98%
“…At the same time, modern biophysical and biochemical tools are also needed to make these same measurements directly on OMPs in their native context within bacteria. En route to this, the use of outer membrane vesicles directly derived from bacteria may provide an excellent stepping stone ( 393 395 ).…”
Section: Concluding Remarks and Open Questionsmentioning
confidence: 99%